PERAN MEDIA AUDIO DALAM IMPLEMENTASI KURIKULUM 2013 MELALUI PEMBELAJARAN TEMA TERPADU DI SEKOLAH DASAR - Faiza Indriastuti (Balai Besar Guru Penggerak Jawa Timur, 2014)
The changes in curriculum KTSP 2006 to the curriculum 2013, had a signifficant impact in the field of education in Indonesia. The signifficant of difference is on its implementation. Implementation of curriculum 2013 for elementary school trough an intregrated learning. The implications for implementation of several components, including teacher, student, materials and learning resources, facilities and infrastructure as well as the selection of instructional methods. The purpose of this writing is to see how the role of instructional audio media in implementation of curriculum 2013 through an integrated thematic learning. Results of review the role of audio instructional media in the implementation of the curriculum 2013 trough an integrated thematic learning are: (1) the use of audio instructional in integrated thematic learning can make the learning process become more ideal, (2) an audio instructional media, can become tools or instructional materials for teacher, to explain the difficult materials, giving concentrate and build a classroom atmosphere, and (3) an audio instructional media in an integrated theme for students of being learning materials to access or repeat information submitted in learning so that it is possible to catch up on some subject matter.Abstrak:Perubahan kurikulum KTSP tahun 2006 menjadi kurikulum 2013, memberikan dampak yang signi kan di bidang pendidikan di Indonesia. Perbedaan yang siginifikan adalah pada implementasinya. Implementasi kurikulum 2013 untuk Sekolah Dasar melalui pembelajaran tematik terpadu. Implementasi tersebut berimplikasi pada beberapa komponen, diantaranya pendidik, peserta didik, materi dan sumber belajar, sarana dan prasarana serta pemilihan metode pembelajaran. Tujuan penulisan ini adalah mengkaji peran media audio pembelajaran dalam implementasi kurikulum 2013 melalui pembelajaran tema terpadu. Hasil kajian peran media audio dalam implementasi kurikulum 2013 melalui pembelajaran tema terpadu diantaranya adalah: (1) penggunaan media audio dalam pembelajaran tema terpadu dapat menjadikan proses pembelajaran lebih ideal, (2) media audio pembelajaran, bagi pendidik dapat menjadi alat bantu atau bahan ajar untuk menjelaskan materi-materi sulit, memberikan contoh konkrit serta membangun suasana kelas, dan (3) media audio pembelajaran dalam tema terpadu bagi peserta didik menjadi bahan belajar untuk mengakses atau mengulang kembali informasi yang disampaikan dalam pembelajaran sehingga dimungkinkan dapat mengejar ketertinggalan pada materi pelajaran tertentu.